An implementation model to guide rural Malawian communities in the scaling-up of an effective HIV prevention programme: an implementation science study - Linda L McCreary, PhD; Diana Jere, PhD; Crystal Patil, PhD; Kathleen Norr, PhD (Elsevier, 2019)
Background: Scaling-up of evidence-based programmes for HIV prevention in areas of high prevalence is a global priority. Many implementation models exist, but a major barrier is the lack of implementation models that are straightforward enough for use by community volunteers who have little education or research experience. Our previous findings have shown the efficacy of a peer-group HIV-prevention programme in Malawi. Now, to shift ownership of this programme from researchers to rural community volunteers, we have adapted an existing implementation model to guide rural Malawi community members in implementation of this programme. Here we describe communities' use of this three-step (Prepare, Roll-out, Sustain) Community Implementation Model (CIM). Methods: We brought together district health, political, and traditional leaders, who agreed to support implementation of the programme; coordinating committees were formed in each community to organise implementation. We conducted workshops to develop leaders' capacities for following the CIM. The committee tracks progress every 6 months, recording the number of benchmarks met from a list of 28. Using a hybrid stepped-wedge design, we simultaneously evaluated three communities' use of the CIM to guide the implementation processes. Findings: By Jan 17, 2019, all three communities had successfully begun implementation using the three-step CIM. During the Prepare step, each community established a coordinating committee, which planned and selected volunteers who were trained as peer group leaders. During Roll-out, peer leaders offered the programme. Two communities have begun the Sustain step, making and carrying out plans to continue and expand the programme. These two communities at the Sustain step have developed capacities needed to keep the programme going. One has submitted a proposal to obtain funding from our project budget; they will soon apply for local funding. The number of benchmarks achieved have steadily increased in all three communities and are shared with local leaders. All three communities have been highly enthusiastic and successful in carrying out the implementation. Interpretation: The CIM is an effective and replicable model to guide future community implementations of this and other health promotion programmes. If the pattern of results seen from two of our three communities continue with the third community, we conclude that the model will support transfer of programme ownership from researchers to community members. Funding: National Institutes of Health/National Institute for Nursing Research R01NR015409 and R01 NR08058.